2004
DOI: 10.1002/jctb.980
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of chlorobenzene using solar and artificial UV radiation

Abstract: In this work photocatalytic degradation of chlorobenzene has been studied using solar and artificial UV radiations. The effect of pH and the presence of different anions on the degradation of chlorobenzene has been studied for both cases. Chlorobenzene has been found to be a strongly adsorbing and hence rapidly degrading species when subjected to photocatalysis. The effect of pH in the range of 3-10 and the presence of different anions at a concentration of 0.1 mol dm −3 on the adsorption was studied. Both pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…Our experimental results are in accordance with data reported by other authors regarding first-order kinetic degradation of some nitroaromatic compounds like mono, di, tri nitrobenzenes, nitrotoluenes and nitrophenols in UV/TiO 2 systems [52][53][54][55][56].…”
Section: Kinetic and Photodegradation Studies Of Nitrobenzene In Watersupporting
confidence: 94%
“…Our experimental results are in accordance with data reported by other authors regarding first-order kinetic degradation of some nitroaromatic compounds like mono, di, tri nitrobenzenes, nitrotoluenes and nitrophenols in UV/TiO 2 systems [52][53][54][55][56].…”
Section: Kinetic and Photodegradation Studies Of Nitrobenzene In Watersupporting
confidence: 94%
“…Details of the columns and mobile phases used are given by Bhatkhande et al (2003a) for NB, Bhatkhande et al (2003b) for CB, and Yawalkar et al (2001) for phenol, respectively. Total organic carbon (TOC) was calculated from HPLC analysis and verified using a Total Organic Carbon Analyzer (ANATOC™-II, Australia).…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between solar and artificial UV irradiation in the photocatalytic degradation of nitrobenzene at equivalent catalyst loading by Bhaktende et al [48] showed a much faster photocatalytic reaction rate under artificial UV radiation even though concentrated sunlight was used. This is as a result of the percentage useful component (UV) present in the artificial lamp used being higher than that in sunlight; however, solar irradiation can show a higher efficiency when visible radiation as well as UV is utilised by the catalyst in the photocatalytic reaction [49].…”
Section: Uv Lampsmentioning
confidence: 98%